Tablet computers for implementing NICE antenatal mental health guidelines: protocol of a feasibility study. Issue 1 (22nd January 2016) - Marcano-Belisario, José S; Gupta, Ajay K; O'Donoghue, John; Morrison, Cecily; Car, Josip
Abstract : Introduction: Depression is one of the most common mental health disorders that may affect women during pregnancy. The prompt identification of this disorder, and the provision of treatment, may help to reduce the likelihood of post-partum depression, prevent severe forms of the disease, and reduce its intergenerational impact. Despite women's repeated encounters with health services throughout their antenatal care, depression often goes undiagnosed. This is one area where mobile health could prove useful. We will assess the feasibility of using tablets to incorporate depression screening into antenatal pathways. We will also assess if survey layout could affect the quality of the data collected through these devices. Methods and analysis: We will test the feasibility of using iPad Airs for the administration of the Whooley questions and the Edinburgh Postnatal Depression Scale (EPDS) to pregnant women attending antenatal clinics in England. We will assess the impact of survey layout on the quality of the responses given to these screening scales using a parallel, randomised controlled study design. We will calculate the positive predictive value, the negative predictive value and the false omission rate of the Whooley questions in comparison with the EPDS. We will calculate differences in data equivalence, time needed to complete the surveys, break-off rates, data completeness and requests for help between the 2 experimental groups: using all questions in one screen and navigation by vertical scrolling, or a single question per screen and navigation by multiple pages. Ethics and dissemination: This study has been approved by the National Research Ethics Service Committee South East Coast—Surrey. Our findings will be disseminated through academic peer-reviewed publications, conferences and discussion with peers.